Pengaruh perbankan konvensional terhadap pertumbuhan ekonomi dengan perbankan syariah sebagai variabel moderating menggunakan SEM-PLS - Widjiantoro, Surya Tegar; Yusuf, Muhammad (AL-Muqayyad, 2025)
Islamic banking assets in Indonesia remain significantly behind conventional banking. In 2023, the assets of conventional banks reached over IDR 11,000 trillion, while Islamic banks accounted for only around IDR 580 trillion. This considerable asset gap motivates further investigation into the roles of both banking systems in economic development. This study aims to examine the influence of conventional banking on economic growth, the impact of Islamic banking on economic growth, and whether Islamic banking moderates the relationship between conventional banking and economic growth. The research employs the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method, using annual secondary data from 2007 to 2023. The findings reveal that conventional banking significantly influences economic growth, while Islamic banking does not have a significant effect. Moreover, Islamic banking does not moderate the relationship between conventional banking and economic growth. These results highlight the need to strengthen the role of Islamic banking to enhance its contribution to national economic development.